ON/OFF metal-triggered molecular tweezers for fullerene recognition. Issue 84 (27th September 2021) - Sacristán-Martín, Adriana; Barbero, Héctor; Ferrero, Sergio; Miguel, Daniel; García-Rodríguez, Raúl; Álvarez, Celedonio M.
Abstract : Turning on the corannulene: fully reversible and quantitative switching of ON/OFF states for fullerene recognition achieved by metal coordination. Abstract : Herein, we report molecular tweezers for fullerene recognition based on 2, 2′-bipyridine-bearing corannulene motifs. The syn or anti confirmation can be selected simply by Cu(i ) coordination/decoordination, thus controlling the fullerene recognition capability of the system on demand and leading to the formation of effective metal-triggered ON/OFF molecular tweezers.